Sialendoscopy in the Management of Radioiodine Induced Sialadenitis: A Systematic Review. (November 2017) - Cung, Thai-Duong; Lai, Wanda; Svider, Peter F.; Hanba, Curtis; Samantray, Julie; Folbe, Adam J.; Shkoukani, Mahdi; Raza, Syed Naweed
Objectives: Salivary gland dysfunction as a consequence of radioiodide ablation is present in as many as two-thirds of patients, and unfortunately, many of these individuals do not respond to conservative measures. Sialendoscopy as a minimally invasive therapeutic modality may have utility in the treatment of radioiodide induced sialadenitis (RAIS). Our aim was to explore whether sialendoscopy resulted in clinical improvement in patients with RAIS. Methods: A systematic review of studies on sialendoscopy for RAIS was conducted using MEDLINE database, Embase, and Cochrane Library. The outcomes of interest included the proportion of patients demonstrating clinical improvement after intervention, patient demographics, radiation dose, specific procedural variations, specific salivary gland, failure rate, and recurrence. Results: Eight studies met inclusion criteria. Data reviewed showed an increased predilection of parotid sialadenitis relative to submandibular gland sialadenitis. All but 2 studies employed sialendoscopy only after failure of conservative measures. An overall rate of clinical improvement ranging from 75% to 100% was reported. Conclusion: This systematic review encompassing 122 patients represents the largest pooled sample to date of patients undergoing sialendoscopy for RAIS. Sialendoscopy represents an invaluable minimally invasive modality that may obviate the need for more invasive surgery as intervention was associated with a high success rate.